[OP.8D.04] COMPARISON STUDY OF CAROTID DISTENSION WAVES MEASURED WITH A NON-INVASIVE OPTICAL FIBRE SENSOR AND AORTIC INVASIVE PRESSURE WAVES. (September 2016) - Leitao, C.; Antunes, P.; Afreixo, V.; Andre, P.; Pinto, L.; Fernandes, R.; Costa, M.; Bastos, J.
Abstract : Objective: The present work aims to test a new optical fibre probe (POFpen) to measure the carotid distension waveform, comparing it with the simultaneously acquired invasive arterial pulses by an intracatheter in the ascending aorta. Design and method: The optical fibre device detects the pulse wave by placing a reflector at the carotid surface, whose distension movements modulate an applied optical signal that is monitored in reflection. Simultaneous acquisitions of distension carotid pulses with the POFpen and invasive pressure catheter in the aortic root were performed in 19 subjects, with an average age of 71 ± 12 years. Both waveforms were normalized [0, 1] and superimposed. The normalized distension wave was calibrated with diastolic and brachial mean pressures to central pressure calculation. This method assumes that, in supine position, diastolic and mean arterial pressures are constant in the proximal arterial tree and the arterial pulse waveform is distorted through the arterial tree, causing pressure amplification, but keeping the same area under the curve. The mean arterial pressure was calculated as diastolic pressure plus one third of pulse pressure. Root-Mean-Square Error (RMSE) was calculated to analyse the similarity between curves. Paired t tests and Pearson correlations between waveforms were performed to compare the harmonic composition (first 8 harmonics) of the signals as well as central pressure assessment using the distension waves. Figure. No caption available. Results: RMSE calculation shown average differences between curves of 20.69 ± 5.12 %. Paired t-test shown that the first 8 harmonics are not significant different between them (p < 0.05). Pearson correlation also shown that the first 6 harmonics are significantly correlated (p < 0.02). For the central pressure comparison, the paired t-tests did not found significant differences between techniques (p < 0.05) and the Pearson correlation was significant (p < 0.01). The calculated central pressure underestimated central pressure in approximately 4%. Conclusions: As expected, the RMSE between of both techniques shows that the curves are different due to the distinct acquisition location, however the frequency components of the aortic pressure are maintained, which translates in a good correlation between both signals, being possible to assess the central pressure from distension curves.